2021
DOI: 10.3390/nano11010151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ni-Pt Alloy Thin Films Prepared by Supercritical Fluid Chemical Deposition Technique

Abstract: Ni-Pt alloy thin films have been successfully synthesized and characterized; the films were prepared by the supercritical fluid chemical deposition (SFCD) technique from Ni(hfac)2·3H2O and Pt(hfac)2 precursors by hydrogen reduction. The results indicated that the deposition rate of the Ni-Pt alloy thin films decreased with increasing Ni content and gradually increased as the precursor concentration was increased. The film peaks determined by X-ray diffraction shifted to lower diffraction angles with decreasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In contrast, two new diffraction peaks appeared at 38.8° and 69.3° in Pt/SiC‐240, belonging to the (200) and (220) crystal planes of Pt nanoparticles. These results indicated the formation of Pt nanocrystal rather than Pt‐SAC under 240 °C heating treatment [36,37] . In addition, XPS measurements were performed to analyze the electronic structure and valence information of Pt atom.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, two new diffraction peaks appeared at 38.8° and 69.3° in Pt/SiC‐240, belonging to the (200) and (220) crystal planes of Pt nanoparticles. These results indicated the formation of Pt nanocrystal rather than Pt‐SAC under 240 °C heating treatment [36,37] . In addition, XPS measurements were performed to analyze the electronic structure and valence information of Pt atom.…”
Section: Resultsmentioning
confidence: 92%
“…These results indicated the formation of Pt nanocrystal rather than Pt-SAC under 240 °C heating treatment. [36,37] In addition, XPS measurements were performed to analyze the electronic structure and valence information of Pt atom. Figure 2b showed that the binding energy of Pt atom in Pt 1 /SiC gradually shifted to higher values with an increase in heating temperature.…”
Section: Synthesis and Characterization Of Pt-sacsmentioning
confidence: 99%
“…Films piezoelectricity and ferroelectric property is confirmed by piezo force microscopy and spectroscopy, which envisions their use as lead-free hybrid energy harvesters. Another synthesis work is presented by Sudiyarmanto and Kondoh in [2]. In this case, supercritical fluid chemical deposition is applied to the production of Ni-Pt alloy thin films.…”
mentioning
confidence: 99%